(untitled) (Communications in Computational Physics, 2018)
We analytically and numerically compute the Onsager dissociation rate (exciton dissociation) on an interface induced by a piezoelectric potential in an inorganic-organic hybrid p-n junction system (ZnO + (poly(p-phenylene vinylene)); PPV). When a positive piezoelectric potential is created at the interface region owing to the deformation of the system, free electrons accumulate at the interface. Hence, screening effects are observed. It is assumed that the electron layer formed at the interface then attracts free holes from the p-type PPV region, which leads to exciton formation, possibly via the Langevin recombination process. The increased exciton density can then contribute to the Onsager dissociation rate, which is maximum around the interface. This paper focuses on the role of piezoelectric effects in promoting exciton formation at the interface and its relation with the exciton dissociation rate.